2021
DOI: 10.1007/s41125-021-00073-5
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Delivery of Police Use of Force Training: A German Case Study

Abstract: The current study aims to investigate the current structure and delivery of police recruit training. Using a case study approach, we systematically observed a semester of police training that consisted of 30 h with a specific focus on police use of force training. Field notes and time-on-task data was analysed using an inductive approach. The results revealed, first, a lack of constructive alignment of the training modules and learning tasks within the training settings. Second, an adherence to traditional lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
2
30
1
2
Order By: Relevance
“…Und wie wird sie in der Praxis gelebt? Beobachtungen aus der Praxis zeigen (Staller et al 2019(Staller et al , 2021c, dass Kommunikation in der polizeilichen Lehr-und Einsatzpraxis vergleichsweise begrenzt aufgefasst wird: sowohl in der sachlichen als auch in der kontextuellen Dimension.…”
Section: Blinder Fleck 3: Die Extension Von Kommunikationunclassified
See 1 more Smart Citation
“…Und wie wird sie in der Praxis gelebt? Beobachtungen aus der Praxis zeigen (Staller et al 2019(Staller et al , 2021c, dass Kommunikation in der polizeilichen Lehr-und Einsatzpraxis vergleichsweise begrenzt aufgefasst wird: sowohl in der sachlichen als auch in der kontextuellen Dimension.…”
Section: Blinder Fleck 3: Die Extension Von Kommunikationunclassified
“…Auch polizeiliche Ausbildungscurricula (z. B. NRW 2018) und praktische Einsatztrainings unterstützen diese Zwei-Welten-Lehre (Staller et al 2019(Staller et al , 2021c: Kommunikation oder Zwangshandeln -oder wie eine aktuelle Publikation titelt: "Kommunikation statt Gewalt" (Lorei 2021).…”
Section: Blinder Fleck 3: Die Extension Von Kommunikationunclassified
“…This conceptualization has created a dominant training paradigm for PST. Research evaluating use-of-force training (e.g., (Koedijk et al, 2019;Cushion, 2020;Staller et al, 2021), shows that officers tend to train isolated skills and techniques first, repeating repetitions of one technique at a time practiced in pairs, before moving on to practice another isolated skill-with Cushion (2020) showing that this type of training form often accounts for the largest proportion of activity in United Kingdom PST. Contemporary learning research and understanding (e.g., Soderstrom and Bjork, 2015) and research examining police training (e.g., Staller and Koerner, 2019) have challenged the assumptions of this approach.…”
Section: Background: Personal Safety Training Learning and Scenario-based-trainingmentioning
confidence: 99%
“…A linear or modular approach that positions techniques/skills first often results in 'end-on-end' or 'blocked' practice; reviews and evaluation studies have shown training in this way is a significant consumer, or even a waste, of training time (O'Neil et al, 2019;Bennell et al, 2020;Cushion, 2020;Staller et al, 2021). Learning requires direct and successful contact with appropriate learning tasks (Carpenter et al, 2012;Cushion, 2020) providing task engagement.…”
Section: Background: Personal Safety Training Learning and Scenario-based-trainingmentioning
confidence: 99%
See 1 more Smart Citation